Pengaruh Karakteristik Marketing Syariah terhadap Keputusan menjadi Nasabah BMT UGT Sidogiri Cabang Pamekasan - Khafiatul Hasanah (Institut Agama Islam Negeri Madura, 2016)
Islamic financial institutions continue to plague the urban to the rural. No exception to the Baitul Maal Wat Tamwil (BMT) in Pamekasan area. Consequently, all the processes required to implement management based on Islamic principles, as well as in marketing. That is why ethics and morals become a necessity in carrying out any business activity. BMT UGT Sidogiri Pamekasan branch is one of the BMT which has increased exponentially customers. Allegedly due to the increase in the number of customers continued to increase customer confidence. One of the flagship products owned BMT UGT Sidogiri Pamekasan branch in collecting funds is Islamic savings have minimum deposit Rp 1000 by the facility pick up the ball that is not offered by other BMT in Pamekasan. Based on this background, researchers interested in conducting research with the title